Properties of the thermoluminescence glow peaks simulated by the interactive multiple‐trap system (IMTS) model. Issue 4 (5th January 2015) - Sadek, A. M.; Eissa, H. M.; Basha, A. M.; Kitis, G.
Abstract Thermoluminescence (TL) glow peaks were simulated over a wide range of absorbed doses using the interactive multiple‐trap system (IMTS) model. The absorbed dose range was divided into three regions; a region in which the measured TL signal grows quadratically with the absorbed dose, a supraquadratic dose‐response region and dose‐saturation region. The properties of the simulated glow peaks were investigated for each dose region. The different behaviors of the maximum peak position (Tmax) with the absorbed doses were discussed. The applicability of applying the general‐order kinetics (GOK), the mixed‐order kinetics (MOK), and the developed one trap–one recombination (OTOR) center expressions on the IMTS glow peaks was investigated. The results showed that, in general, the developed OTOR expressions are the most apt expressions to be used in the peak‐fitting method for the deconvolution of the experimental glow curves. The accuracy of the GOK and MOK expressions in describing the IMTS glow peaks is dependent on the value of the ratio of the trapping probability to the recombination probability (R = A1/Am) and the amount of the absorbed dose. New TL expressions based on the non‐interactive multiple‐trap system (NMTS) model were deduced.